Understanding Human Resource Management (HRM): Definition and Function - Andi Asrizal; Herni Widiyah Nasrul; Oktavianti Oktavianti (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to identify and understand the concept of Human Resource Management (HRM) and its function in supporting organizational effectiveness. HRM plays a crucial role in managing individual potential to optimally contribute to achieving organizational goals. Using a quantitative approach, this study analyzes respondents' perceptions of key HRM dimensions, including planning, recruitment and selection, training and development, performance appraisal, and compensation. Data were collected through a Likert-scale questionnaire and analyzed using descriptive analysis techniques and simple linear regression to determine the influence of HRM functions on organizational effectiveness. The results indicate that all HRM functions have a positive and significant relationship with increased productivity and organizational performance. This finding confirms that effective human resource management is a strategic factor in maintaining organizational sustainability and competitiveness. This study is expected to enrich the HRM literature and serve as a reference for practitioners in designing professional, adaptive, and performance-oriented workforce management strategies.